Social Infrastructure Provision Assessment as a Tool for Implementing Provincial Socio-Economic Policy - O. N. Misko; A. B. Elatskov; V. N. Moskalenko (Управленческое консультирование)
This article outlines the concept of a tool for the implementation of socio-economic policy and considers the assessment of social infrastructure provision of the population as one of them, namely a systemic feedback tool. The paper discusses the importance of social infrastructure for the socio-economic development of the province and the methods of assessing the provision of the population with it, identifies the main stages of this procedure and its relationship with other key tools, which is presented in the form of a graphical scheme; discusses the main tasks and features of rationing of indicators as a procedure for developing a reference measure of assessment; discusses and systematizes the main approaches to the calculation of socio-infrastructural provision. At the same time, not infrastructure objects, but more fractional units — elements — are taken as calculation units. It is proposed to systematize various calculation methods in the form of a matrix depending on the arguments used.